Castles and Fortresses in Bilad al-Sham during the Crusader Rule through the book of Al-Idrisi’s Book (Died 560AH/1164AD): Nuzhat al-Mushtāq fi Ikhtirāq al-Āfāq - Mosa, Mona; AbdulKarim, Mamoun (Al-Adab Journal, 2024)
Al-Idrisi dealt with an accurate description of the geography of the cities and terrain of the Levant and the nature of its people, and he happened to visit it; The submission of some parts of it to the Crusader occupation, therefore; He is considered among the most important historians who dealt with that important and critical era and referred to the conditions of the Levant under the Crusader rule. The research relied on the method of historical research in its two parts, description, and analysis, which is based on collecting scientific material related to the subject of research from its various sources, then criticizing it, deriving facts from it, defining its dimensions, and analysing it in order to reach the consequences of it, then arranging and formulating it to produce it in its final form. The research relied on a several sources in addition to contemporary sources related to the subject of the research.